Riscos psicossociais envolvidos na organização do trabalho de servidores da Fundação de Vigilância da Saúde do Estado do Amazonas - Queiroz, Paula Talita Farias (Brasil, 2024)
In this research, we sought to analyze the Work Organization of health workers from a public institution from the theoretical approach of Work Psychodynamics. As a methodological tool, the Work Organization Scale of the Psychosocial Risk Assessment Protocol (PROART) was used. A total of 225 workers who responded to PROART participated in the study and the data were statistically analyzed. By analyzing the Work Organization in general in the FVS, we sought to focus on the division of tasks among the employees, as well as to identify deleterious aspects of their working conditions and to estimate the social division of labor among them in this institution. The results indicate that the division of tasks presented a medium risk and the social division of labor, a low psychosocial risk. It is concluded that Proart was a tool of relevant contribution and provided the opportunity to survey points that need to be on alert and others that are already working and need to be maintained or even improved, if possible, within the Health Surveillance Foundation.